How to conduct good quality research on violence against children with disabilities: key ethical, measurement, and research principles - Kyegombe, Nambusi; Banks, Lena Morgon; Kelly, Susan; Kuper, Hannah; Devries, Karen M. (BMC public health, 2019)
Background Approximately one billion children experience violence every year. Violence against children is an urgent global public health concern and violation of children’s rights. It is also a risk factor for serious negative health and social outcomes and is therefore addressed within the Sustainable Development Goals (SDGs). Children with disabilities, who make up one in 20 children worldwide, are particularly vulnerable to violence although good quality data are lacking on causes and means of prevention of violence against children with disabilities. Key challenges exist in the measurement of disability and violence, which in part explains the dearth in evidence. Improving research on violence against children with disabilities This paper provides guidance on how to conduct good quality, ethical, and inclusive research on violence against children with disabilities, particularly in low-income settings. The lack of an international agreed ‘gold standard’ frustrates efforts to measure violence across settings and time. Careful consideration must be given to the design of survey tools. Qualitative and participatory research methods also offer important opportunities to explore children’s subjective understanding and experiences of violence. Challenges also exist around the measurement of disability. Disability may be measured by asking directly about disability, through self-reported functioning, or through the presence of impairments or health conditions. These approaches have strengths and limitations and should build on what children are able to do and include appropriate adaptations for specific impairments where necessary. Ethical research also requires adherence to ethical guidelines and approvals, obtaining informed consent, appropriate child protection responses, and careful consideration of interviewer-related issues including their selection, training, and welfare. Key methodological gaps remain - how to include children with severe communication challenges in research; how to respond in instances of weak child protection systems; designing sampling procedures that adequately represent children with disabilities in large-scale violence surveys; and determining how best to ask about violence safely in large-scale surveys and monitoring data. This paper further advocates for the dissemination of research results in inclusive and accessible formats. Conclusion With careful planning, challenges in collecting data on disability and violence can be overcome to generate evidence in this neglected area.